2016
DOI: 10.1620/tjem.239.237
|View full text |Cite
|
Sign up to set email alerts
|

A Chronological Increase in Gastric Acid Secretion from 1995 to 2014 in Young Japanese Healthy Volunteers under the Age of 40 Years Old

Abstract: Gastric acid secretion levels are an important determinant of the manifestation of acid-related upper GI diseases such as gastroesophageal reflux disease. We recently reported that gastric acid secretion levels did not change from the 1990s to 2010s in H. pylori-negative asymptomatic Japanese outpatients with a mean age of 63 years old. However, because young people have a quite different lifestyle, including dietary pattern, from elderly people in Japan, it is worth investigating any chronologic changes in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…This may be because gastric acid secretion is increasing due to a decrease in H. pylori (HP) infection [28]. Furthermore, Iijima et al reported that gastric acid secretion in young people who are negative for HP infection is also increasing [29]. Schneider and Corley reported that the continuing decline in HP infection could lead to the disappearance of duodenal ulcers and distal gastric cancers and a marked increase in GERD, Barrett's esophagus, and BEA [30].…”
Section: Discussionmentioning
confidence: 99%
“…This may be because gastric acid secretion is increasing due to a decrease in H. pylori (HP) infection [28]. Furthermore, Iijima et al reported that gastric acid secretion in young people who are negative for HP infection is also increasing [29]. Schneider and Corley reported that the continuing decline in HP infection could lead to the disappearance of duodenal ulcers and distal gastric cancers and a marked increase in GERD, Barrett's esophagus, and BEA [30].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in GERD identified in this study may reflect the increase in gastric acid secretion associated with the changes in diet and reduction of H. pylori in Japan. 10,12,20 An increase in gastric acid secretion could also be responsible for the proportion of GERD patients with endoscopic Barrett's esophagus significantly increasing between the two periods (i.e. 24/45 [53.3%] vs 8/31 [25.8%], P = 0.017) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that between 1995 and 2014 the level of gastric acid secretion increased in healthy young Japanese, 10 whereas over the last 40 years, the age‐specific severity of gastric atrophy and gastric mucosal intestinal metaplasia has declined remarkably 11 . This trend has been most marked in young adults (20–39 years).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One possible reason for this change is an increase in gastric acid secretion in the Japanese population, irrespective of Helicobacter pylori infection [ 18 ]. Since dietary fat intake has been reported to stimulate gastric acid secretion in mice [ 19 ], the chronological increase in gastric acid secretion in Japanese people may be related to an increase in fat intake [ 20 ]. In addition, because H .…”
Section: Discussionmentioning
confidence: 99%